Towards A Theory of Why Kids Run Away: Evaluating Strain and Control Mechanisms to Account for First-time Running Behavior Among Males vs. Females. Issue 3 (4th March 2023) - Coward Bucher, Carrie; Manasse, Michelle; Rebellon, Cesar J.
ABSTRACT: Between 5–9% of American adolescents experience 1+ episode of independent homelessness. Although multiple stressors have consistently been shown to precede runaway behavior, sampling homeless populations fails to capture variation between juveniles who run/do not run. This research uses Waves I and II of the Add Health public use data to examine conditions likely to result in a first-time run among males vs. females. Specifically, we argue that strains/negative emotion derived from Agnew's general strain theory and social controls derived from Hirschi's social bond theory will act as positive and negative motivations, respectively, to predict first-time runs. We find significant, main effects on running for multiple strain and control measures. However, results of our integrated models suggest that, while composite strain and depression increase the odds of running across gender, composite social control is associated with lower odds of running for females only. This finding underscores prior research suggesting that social bonds may have a stronger protective impact on females considering a first-time run.